2020
DOI: 10.3389/fcomm.2020.00014
|View full text |Cite
|
Sign up to set email alerts
|

Fear-Free Cross-Cultural Communication: Toward a More Balanced Approach With Insight From Neuroscience

Abstract: In cross-cultural communication and adjunct disciplines such as cross-cultural management and international business, there is a negativity bias of seeing cultural differences as a source of potential issues. The emergence of Positive Organizational Scholarship (POS) questions this problem-focused approach. This paper contributes to the ongoing discussion from neuroscience's perspectives in several ways. Firstly, it provides a neurological look at this bias. Secondly, it proposes that the problem-focused appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 181 publications
0
1
0
1
Order By: Relevance
“…Proposing a shift of paradigm, Nguyen-Phuong-Mai (2019 , 2020) argued that humans are both product and producer of culture, in the sense that individuals are influenced by cultures, yet they can also proactively and deliberately be change agents, re-shaping both themselves and the cultures around them. While Hofstede, embracing the static paradigm, insisted that culture is the software of the mind, the dynamic paradigm and its evolving nature suggested that “not culture, but context is the software of the mind” ( Nguyen-Phuong-Mai, 2017a , 2020 ). This notion of a dynamic culture allows the possibility of bias preventive strategies in which people are “rapid niche constructors” ( Huebner, 2016 ).…”
Section: Further Discussionmentioning
confidence: 99%
“…Proposing a shift of paradigm, Nguyen-Phuong-Mai (2019 , 2020) argued that humans are both product and producer of culture, in the sense that individuals are influenced by cultures, yet they can also proactively and deliberately be change agents, re-shaping both themselves and the cultures around them. While Hofstede, embracing the static paradigm, insisted that culture is the software of the mind, the dynamic paradigm and its evolving nature suggested that “not culture, but context is the software of the mind” ( Nguyen-Phuong-Mai, 2017a , 2020 ). This notion of a dynamic culture allows the possibility of bias preventive strategies in which people are “rapid niche constructors” ( Huebner, 2016 ).…”
Section: Further Discussionmentioning
confidence: 99%
“…En los negocios internacionales, el intercambio de conocimientos, el desarrollo y mantenimiento de relaciones, la negociación de acuerdos y el establecimiento y preservación de asociaciones son logrados gracias a la comunicación intercultural (Szkudlarek et al, 2020). Sin embargo, existe el sesgo inconsciente negativo de percibir la diversidad cultural como fuente de problemas potenciales (Nguyen-Phuong-Mai, 2020). Si bien México y España gozan de una afinidad cultural importante gracias a los lazos históricos, lingüísticos y comerciales, la herramienta de Hofstede Insights (2021) comprueba que existen diferencias entre los puntajes entre ambos países.…”
Section: Introductionunclassified